A Marketable Leadership Strategy in Service Business; Case Study at KBIHU Nurul Haramain Kraksaan Probolinggo - Rifa'i, Moh.; Saad, Mukhlisin; Hasanah, Lutfiyatul; Aisyah, Rasyidah Nur (Tribakti: Jurnal Pemikiran Keislaman, 2021)
Realizing marketable guidance in pilgrimage leadership is not easy to put into practice. It takes a leadership strategy that has positive implications for each congregation that he leads so that it has an impact on increasing the volume of pilgrims every year. This research used a qualitative approach, with a descriptive type. The research data source was obtained from KBIHU Nurul Haramain by purposive sampling and snowball sampling model. The data collection technique was carried out by using observation, interviews, and documentation. While the technical data analysis was by collecting data, reducing data, and drawing conclusions. The validity of the data used a triangulation model. The research results explained that the marketable leadership strategies carried out by the kyai, are: service strategies that are easy to understand by implementing Hajj exercises or rituals 12 times in 1 year and in collaboration, the Hajj practice directly led by Kyai and professionals, direct guidance from home to the holy lands of Makkah and Medina, arranging rituals scheduled as needed the knowledge systematically. Strategies of figures that appear in the Kyai consist of namely friendly service, and excellent facilitation for the congregation from in the country to the holy land.